The northward path of ambition : the Northwest Passage and why Canada needs to re-embrace liberal internationalism in the Arctic - Heffernan, Nicolas (Univerzita Karlova, Fakulta sociálních věd, 2014)
Cílem této práce je analyzovat současný Arctic zahraniční politiku Kanady, se zaměřením na jeho úsilí tvrdí, Northwest průchod, jak vnitřních vod, z kritického pohledu.Konečným závěrem bude, že Kanada by se měla přesunout od své současné složité neorealismu přístupu a znovu přijmout liberální internacionalismus, aby bylo možné formulovat nejefektivnější Northwest Passage režim. Powered by TCPDF (www.tcpdf.org) Seen as a valuable shortcut from Europe to Asia, the Northwest Passage could become an important shipping route, and Canada wants to be able to control it. However, the current Conservative Party government under Prime Minister Stephen Harper has led an aggressive, complex neorealist approach to securing sovereignty over the Passage consisting of loud diplomacy, military drills, and rejection of multilateral cooperation in the region. But this strategy that perceives Canada as a principle power is not sustainable. The government must accept that Canada simply cannot afford to unilaterally control and develop the Northwest Passage, and a liberal internationalist approach is what is needed. Rather than continuing to fight for international acknowledgment that the Passage is a domestic strait, Canada needs to recognize that the strait can be managed and developed much more effectively if it oversaw a multilateral development effort through the International Maritime Organization. This thesis will consist of five chapters: 1. The history of Canada and the Northwest Passage, 2. The benefits of a more accessible Arctic, 3. Challenges to developing a more open Arctic, 4. Three theoretical perspectives of Canadian foreign policy, 5. Returning to multilateralism: and effective Northwest Passage policy. Powered by. Department of Political Science Katedra politologie Fakulta sociálních věd Faculty of Social Sciences